EFFECT OF ADDING DIFFERENT LEVELS OF ROSE WATER IN BROILER DRINKING WATER ON CARCASS PERFORMANCE AND SOME HISTOLOGICAL TRAITS IN ROSS308 - Jassim, Mahmoud Khalaf; Al-Hassani , Ali Sabah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this research is to study the effect of using different concentrations of aqueous extract of damask flowers on the ratios of some major and minor parts and some histological qualities. There are a few studies on the effect of the use of rose water in various agricultural animals. 250 one-day-old commercial ross308 broiler chicks were randomly divided into 5 groups of 50 birds. In the treatment (T1control treatment) plain water was used without additives, while in the transactions T2, T3, T4 and T5 rose water was added to drinking water at a concentration of 5%, 10%, and 5% for 12 hours, and 10% for 12 hours, respectively. The results showed the superiority of coefficients T2 and T5 in live body weight, the percentage of clearance with and without the presence of eaten viscera, the percentage of drummer's stick, the percentage of chest piece and the rest of the other pieces, as well as a significant increase in the height of the villi and the depth of the crypts for the second and fifth coefficients compared to other coefficients at (P≥ 0.05) .